Engineering management in a global environment : guidelines and procedures - Atesmen, M. Kemal (Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T & F Informa, plc, 2017)
Annotation In today's global business environment with high speed interactions, engineering organizations are evolving continuously. Engineering Management in a Global Environment: Guidelines and Procedures provides guidelines for changing roles of engineering managers in the international arena. The book covers global, multidisciplinary, and flat engineering organizations. Recommended procedures for hiring, mentoring, work assignments, and meetings in the global arena are detailed. Guidelines for keeping up with technology and with the changing world, performance reviews, layoffs, necessary engineering tools, and work atmosphere are discussed. Procedures for engineering team building and for having good relationships with upper management, customers, subcontractors, and regulatory agencies are provided. Each chapter ends with a checklist summarizing engineering managerial guidelines in that chapter.
Includes index.
Keywords: Engineering -- Management.; International business enterprises -- Management.; elektronické knihy; electronic books